A rare discovery of Spigelian-cryptorchidism syndrome in adult - Rajan Gurung; Aishath Azna Ali; Fei, Yee Lee; Aung Mra; Mohd Firdaus Mohd Hayati (Elsevier Inc., 2021)
Spigelian hernia (SH) occurs due to the protrusion through a congenital or acquired defect or weakness in the Spigelian aponeurosis. SH accounts for only 0.1–0.4% of occurrence and a 17–24% risk of strangulation. We hereby report a case of a 34-year-old gentleman presented with concomitant incarceration of the omentum with small intestine and testis in Spigelian hernia sac. We have successfully operated on this patient via a transperitoneal approach with a small incision over the hernia site. This incision could be an alternative to midline laparotomy as a safe and effective method in managing incarcerated SH in an emergency setting.